Specifics of Tax Law Drafting on Selected Issues from the Czech Republic - Radvan, Michal (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
The contribution is dealing with some of the specifics of tax law drafting. It aims to show some problematic issues connected with tax law drafting in the Czech Republic in the last two decades and clarify tax law drafting principles. To achieve the objectives, it defines tax law drafting principles and sums up if the Czech legislator follows them. In gives many examples and describes and critically analyzes the institutes affected by the ignorance of these principles. It is possible to conclude that there is no need to clarify the principles of tax law drafting. To achieve a good quality of tax law, it seems to be enough to follow the principles. The practice should be changed mainly in several areas: 1. Fixed tax rates should be replaced by the percentage tax rates, or there should be specific rules in each act on how the tax rates should be changed with regard to inflation; 2. Vacatio legis for tax law must be incorporated, probably directly in the Constitution; 3. Some tax bills should be voted under so-called close rules, i.e., a “yes or no vote” without the possibility of introducing amendments.